Study of Significance of Echocardiography and Estimation of Serum Ferritin Levels in Beta-thalassemia Major Patients - Shahana Khanum; A.N. Thobbi (Al Ameen Medical College, 2023)
Objectives: Mean prevalence of thalassemia is nearly 3.5%. Approximately 4% of world's population is carrier of alpha and beta thalassemia. Cardiac complications are the most common cause of death in β-Thalassemia major. In India, studies regarding screening of cardiac complications in first decade by echocardiography are minimal. This study was done to assess the significance of Echocardiography in early detection of cardiac complications in Beta-thalassemia major patients. Methods: This study was conducted from March-2021 to October-2022 on 60 Beta-Thalassemia major patients aged between 2 to 18 years coming to Al-Ameen Medical College Hospital, Vijayapura. Patients with congenital heart disease or terminal illness were excluded. After detailed history and clinical examination, investigations were done; which included complete blood count, serum ferritin estimation, Chest X-ray, Electrocardiography and Echocardiography. Patients were categorized into two age groups, 2-9 years and 10-18 years respectively and the results were compared. Results: 71.67% (n=43) patients had increased Left Ventricular Mass of which 40% (n=24) belonged to 10-18 years and 31.67% (n=19) belonged to 2-9 years age group. Among 16.67% (n=10) patients who had pulmonary hypertension, 10% (n=6) belonged to 10-18 years and 6.67% (n=4) belonged to 2-9 years age group. Correlation of Serum ferritin levels with Cardiac abnormalities was statistically insignificant. Conclusion: Cardiac complications can occur in first decade also secondary to chronic anaemia and iron overload. Whereas Serum Ferritin levels are not representative of cardiac abnormalities, Echocardiography should be used as screening tool in asymptomatic Beta-Thalassemia major patients even in first decade of life.